Engineering of a hybrid nanoparticle-based nicotine nanovaccine as a next-generation immunotherapeutic strategy against nicotine addiction: A focus on hapten density. (April 2017) - Zhao, Zongmin; Powers, Kristen; Hu, Yun; Raleigh, Michael; Pentel, Paul; Zhang, Chenming
Abstract: Although vaccination is a promising way to combat nicotine addiction, most traditional hapten-protein conjugate nicotine vaccines only show limited efficacy due to their poor recognition and uptake by immune cells. This study aimed to develop a hybrid nanoparticle-based nicotine vaccine with improved efficacy. The focus was to study the impact of hapten density on the immunological efficacy of the proposed hybrid nanovaccine. It was shown that the nanovaccine nanoparticles were taken up by the dendritic cells more efficiently than the conjugate vaccine, regardless of the hapten density on the nanoparticles. At a similar hapten density, the nanovaccine induced a significantly stronger immune response against nicotine than the conjugate vaccine in mice. Moreover, the high- and medium-density nanovaccines resulted in significantly higher anti-nicotine antibody titers than their low-density counterpart. Specifically, the high-density nanovaccine exhibited better immunogenic efficacy, resulting in higher anti-nicotine antibody titers and lower anti-carrier protein antibody titers than the medium- and low-density versions. The high-density nanovaccine also had the best ability to retain nicotine in serum and to block nicotine from entering the brain. These results suggest that the hybrid nanoparticle-based nicotine vaccine can elicit strong immunogenicity by modulating the hapten density, thereby providing a promising next-generation immunotherapeutic strategy against nicotine addiction. Graphical abstract: